Evidence for PTGER4, PSCA, and MBOAT7 as risk genes for gastric cancer on the genome and transcriptome level. (6th September 2018) - Heinrichs, Sophie K. M.; Hess, Timo; Becker, Jessica; Hamann, Lutz; Vashist, Yogesh K.; Butterbach, Katja; Schmidt, Thomas; Alakus, Hakan; Krasniuk, Iurii; Höblinger, Aksana; Lingohr, Philipp; Ludwig, Monika; et al.
Abstract: Genetic associations between variants on chromosome 5p13 and 8q24 and gastric cancer (GC) have been previously reported in the Asian population. We aimed to replicate these findings and to characterize the associations at the genome and transcriptome level. We performed a fine‐mapping association study in 1926 GC patients and 2012 controls of European descent using high dense SNP marker sets on both chromosomal regions. Next, we performed expression quantitative trait locus (eQTL) analyses using gastric transcriptome data from 143 individuals focusing on the GC associated variants. On chromosome 5p13 the strongest association was observed at rs6872282 ( P  = 2.53 × 10 −04 ) and on chromosome 8q24 at rs2585176 ( P  = 1.09 × 10 −09 ). On chromosome 5p13 we found cis‐eQTL effects with an upregulation of PTGER4 expression in GC risk allele carrier ( P  = 9.27 × 10 −11 ). On chromosome 8q24 we observed cis‐eQTL effects with an upregulation of PSCA expression in GC risk allele carrier ( P  = 2.17 × 10 −47 ). In addition, we found trans‐eQTL effects for the same variants on 8q24 with a downregulation of MBOAT7 expression in GC risk allele carrier ( P  = 3.11 × 10 −09 ). In summary, we confirmed and refined the previously reported GC associations at both chromosomal regions. Our data point to shared etiological factors between Asians and Europeans. Furthermore, our data imply an upregulated expression of PTGER4 and PSCA as well as a downregulated expression of MBOAT7 in gastric tissue as risk‐conferring GC pathomechanisms. Abstract : Genetic variants at chromosome 5p13 and 8q24 contribute to gastric cancer (GC) risk. Expression quantitative trait loci (eQTLs) involving PTGER4 (5p13), PSCA (8q24), and MBOAT7 may act as underlying pathomechanisms.